Free, Prior and Informed Consent: Consensus or Contention within the Corporate Domain? - Sjogren, Rosalind (2009)
This paper seeks to contribute to the limited Corporate Social Responsibility literature on the subject of indigenous peoples’ right to free, prior and informed consent to mining sector projects. Within the already contested field of corporate human rights responsibilities, free, prior and informed consent is a particularly controversial area, comprising as it does sensitive components of self-determination, group and cultural rights, and disputed land entitlements.